2019
DOI: 10.1111/bju.14757
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from a single‐surgeon series of paediatric robot‐assisted laparoscopic urological procedures: predictors of high‐grade postoperative complications

Abstract: Objectives To describe postoperative complications after robot‐assisted laparoscopic urological surgery in children, and identify potential predictors of these complications by analysing the outcomes of a large‐volume single‐surgeon experience. Patients and Methods We reviewed our institutional database to identify all robot‐assisted laparoscopy (RAL) cases performed between December 2007 and December 2017. Patients were grouped into three cohorts based on the anatomical location of the procedure: upper urinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Large cohort studies in urology report a complication rate ranging from 3% to 19%. As in our study, the most frequently reported postoperative complications were urinary tract infections 16,36–38 . Compared with the open approach, however, robotic surgery may decrease the number of postoperative infections 37 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Large cohort studies in urology report a complication rate ranging from 3% to 19%. As in our study, the most frequently reported postoperative complications were urinary tract infections 16,36–38 . Compared with the open approach, however, robotic surgery may decrease the number of postoperative infections 37 .…”
Section: Discussionsupporting
confidence: 61%
“…As in our study, the most frequently reported postoperative complications were urinary tract infections. 16,[36][37][38] Compared with the open approach, however, robotic surgery may decrease the number of postoperative infections. 37 ENT surgery showed the highest rate of complications in our study, although they were minor.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the development of science and technology, minimally invasive surgery has become one of the mainstream directions in the development of urology, in which robotic surgery, as a new minimally invasive surgical method, is gradually being applied in the field of surgery [ 1 ]. The da Vinci surgical system (DVSS) is widely used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%